Предмет: Математика,
автор: nezukonezuko625
78–3(5+4(x–3))+10 = 6+5(3x–1)
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
78 - 3(5 + 4(х - 3)) + 10 = 6 + 5(3х - 1)
78 - 3(5 + 4х - 12) + 10 = 6 + 15х - 5
78 - 15 - 12х + 36 + 10 = 1 + 15х
109 - 12х = 1 + 15х
-12х - 15х = 1 - 109
-27х = -108
х = -108 : (-27)
х = 4
nezukonezuko625:
спс
Похожие вопросы
Предмет: Окружающий мир,
автор: йхцвпр
Предмет: Английский язык,
автор: aalexa2015
Предмет: Окружающий мир,
автор: 1974207
Предмет: Русский язык,
автор: Evelinka51